2012
DOI: 10.1021/cm203000u
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Triggered Multidrug Release by Hybrid Mesoporous Silica Nanoparticles

Abstract: The treatment of complex diseases such as cancer pathologies requires the simultaneously administration of several drugs in order to improve the effectiveness of the therapy and overwhelm the defensive mechanisms of tumor cells, responsible of the apparition of multidrug resistance (MDR). In this manuscript, a novel nanodevice able to perform remotely controlled release of small molecules and proteins in response to an alternating magnetic field has been presented. This device is based on mesoporous silica nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
215
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(221 citation statements)
references
References 64 publications
4
215
0
2
Order By: Relevance
“…Vallet-Regí and coworkers were able to demonstrate the release of both proteins and small molecules in response to an alternating magnetic field and changes in temperature [55]. Magnetic iron oxide nanocrystals were imbedded inside the silica matrix of MSN and the MSN surface was functionalized with the thermally responsive block copolymer poly(ethyleneimine)-b-poly(N-isopropylacrylamide) (PEI/PNIPAM).…”
Section: Magnetic and Thermal Stimuli Responsive Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vallet-Regí and coworkers were able to demonstrate the release of both proteins and small molecules in response to an alternating magnetic field and changes in temperature [55]. Magnetic iron oxide nanocrystals were imbedded inside the silica matrix of MSN and the MSN surface was functionalized with the thermally responsive block copolymer poly(ethyleneimine)-b-poly(N-isopropylacrylamide) (PEI/PNIPAM).…”
Section: Magnetic and Thermal Stimuli Responsive Systemsmentioning
confidence: 99%
“…As temperature increased above the LCST, the pores opened and a significant increase in protein release occurred due to polarity inversion (hydrophilic to hydrophobic transition) and three-dimensional polymeric changes in the network. Thus, the authors concluded that the phase transition of the polymer acted as the gatekeeper, allowing or preventing the release of macromolecules attached into the polymer branches [55].…”
Section: Magnetic and Thermal Stimuli Responsive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that developing novel multifunctional vectors, which transform their physicochemical properties in response to various stimuli in a timely and spatially controlled manner, is highly desired to translate the promise of gene therapy for clinical success. The temperature-sensitive NPs have been identified, many of them including heat activable iron oxide and thermosensitive polymers [537 -547] , silica NPs [542,544,548] , liposomes [548 -550] , micelles [551] , multifunctional NPs containing both CdTe QDs, and Fe 3 O 4 magnetic particles [552] .…”
Section: Perspectives: Multimodal Theranostic Npsmentioning
confidence: 99%
“…Over the past several years, significant advancements have been made with regards to the synthesis and tunability of functionalized drug carriers, switches, membranes, containers, pumps, and valves. 1,3,[5][6][7][8][11][12][13][26][27][28][29][30] State of the art implantable micro-devices include reservoir-based systems, controlled-release microchips, and various electrically powered microsystems. 1,2,10,31 Osmotic pumps present a convenient and reliable cost-effective drug delivery method capable of replacing repeated injections of soluble and poorly soluble drugs 32,33 for the treatment of chronically debilitating diseases.…”
mentioning
confidence: 99%